PENERBITAN BANK GARANSI PADA LEMBAGA PERBANKAN MENURUT UNDANG – UNDANG NOMOR 10 TAHUN 1998 - Ali Husni (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstractProvision of Bank Guarantee is one of the functions of the Bank, in addition to the function of providing a wide range of banking services. As a policy, the Bank Guarantee given to customers of the Bank with the aim of providing assistance that are pertinent customer support who will perform work tasks that are very limited and selected. Bank to Bank Guarantee issuing a written acknowledgment that it agreed to adhere to the insured in order to fulfill the obligation secured within a certain period of time and with certain requirements in the form of payment of a certain sum of money in the future is assured if it did not fulfill its obligations to the recipient warranty or guarantee in the future if it turns default (default). Provision of Bank Guarantee is one of the functions of the Bank, in addition to the function of providing a wide range of banking services. As a policy, the Bank Guarantee given to customers of the Bank with the aim of providing assistance that are pertinent customer support who will perform work tasks that are very limited and selected.